Figurative Language In Song Lyrics Of Mini Album Butter BTS - Komang Wulan Astriwedayanti; I Made Rajeg; Putu Ayu Asty Senja Pratiwi (CV. Ulil Albab Corp, 2022)
The title of this study is Figurative Language in Song Lyrics of Mini Album Butter BTS. It aims to analyze the types of figurative language expressed in the song lyrics of the BTS’s mini-album “Butter”, the first English single album by BTS. Two songs have been chosen as the data source, “Butter” and “Permission to Dance”. The data were collected using the documentation method and note-taking technique. A descriptive qualitative method was applied in analyzing them using the theory of figurative language proposed by Perrine (1977). The results show that six types of figurative language were found in the mini-album “Butter”. They are simile, metaphor, symbol, hyperbole, personification, and irony.